Nursing intervention in insulin administration: telephone follow-up - Becker,Tânia Alves Canata (2012)
OBJECTIVE: To analyze the competency of people with diabetes mellitus to perform the insulin administration process, before and after telephone monitoring. METHODS: A quantitative, observational, longitudinal, comparative study. Participants were 26 people enrolled in the at-home capillary glycemia self-monitoring program. Data collection occurred in three phases, in January and February of 2010, for a period of 30 days for each person, by means of interview guided by a data collection instrument and an intervention manual. RESULTS: Of the 38 (100%) questions referring to the insulin administration process, telephone monitoring was demonstrated to be efficient in 30 (78.9%), but in 19 (50%) the intervention was statistically significant (p<0.05), in 11 (28.9%) there were no errors in responses to the final competency evaluation, and seven (18.4%) were not amenable to intervention. CONCLUSION: Telephone mornitoring was effective, as a nursing intervention strategy for the insulin administration process in the home.